Pemanfaatan Minyak Biji Kelor (Moringa oleifera L.) pada Pembuatan Sabun Padat Transparan: Utilization of Moringa Seed Oil (Moringa oleifera L.) in Making Transparent Solid Soap - Hardiyanti, Putri; Nurhaeni, Nurhaeni; Hardi, Jaya (Jurnal Teknologi Agro-Industri, 2022)
Moringa seed oil is rich in oleic acid which has benefits for treating skin health. The use of Moringa seed oil as a basic ingredient for making transparent solid soap increases the advantages of soap because it has moisturizing and skin softening properties as well as antimicrobial. The manufacture of transparent solid soap based on Moringa seed oil aims to determine the mass of Moringa seed oil which produces solid soap with the highest foam and pH stability values, as well as the level of soap irritation. The study was conducted using a completely randomized design (CRD) with the independent variable being the mass of Moringa seed oil consisting of four levels of 27.5 grams (A1), 30 grams (A2), 32.5 grams (A3), and 35 grams (A4), while the dependent variables include foam stability and pH stability which were determined after 3 weeks of testing. The best formula was further tested with a solid soap irritation level test. The best formula for transparent solid soap was found in using 30 grams of Moringa seed oil (A2) with foam stability of 93.56%, pH stability of 9-9.6, and low irritation level of only 20% after five days of use.